Aerosol measurements during OASIS Barrow field intensive Spring 2009, Version 1.0 ... - Smith, J.; Sjostedt, S.; Abbatt, J.; Wiedensohler, A. (UCAR/NCAR - Earth Observing Laboratory, 2012)
The NCAR "Particle Size Distribution" (PSD) instrument consists of three instruments that measure the size distribution of the ambient aerosol from 3 nm to 2 microns. General specifications for the instrument during Ocean-Atmosphere-Sea Ice-Snowpack (OASIS) are as follows: * Size range: ~3.85 nm to 2 micron * Number of diameter bins: 75 * Time resolution: 5 min Please see included documentation for full details. ...